SOFTWARE APPLICATION FOR CALCULATING MODELS FORECASTING INNOVATIVE DEVELOPMENT OF INDUSTRIES - M. M. Mirzemagomedova; M. M. Muradov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The article is devoted to the development of a software application that allows you to automate methods for collecting and processing information, as well as perform time-consuming analytical calculations. Embarcadero C ++ Builder XE, a visual object-oriented programming language, was used to implement a software application. The software being developed is created to solve the following tasks: a comparative analysis of innovative development indicators for the selected years; selection of a projected indicator, building a regression model; making a forecast with a lead time of 3; determination of the confidence interval; the formation of a graphical display of observable and calculated values, the selected indicator of innovative development.Method. In a software application, formalized methods were used as a mathematical model, one of which is multiple regression. Regression analysis consists in defining an analytical expression of a relationship in which a change in a single quantity, called a dependent or productive attribute, is due to the influence of one or several independent quantities (factors).Result. With the help of the developed software product, you can not only automate time-consuming methods of collecting and processing information, but also per-form complex analytical calculations using the multiple regression method.Conclusion. Embarcadero C ++ Builder XE is by far the latest state-of-the-art technology and C ++ programming environment. With C ++ Builder, XE has become faster to do the job of creating high-quality applications for Windows-based applications, due to the rapid writing of code, new tools and components.